Strategi Pemasaran Dalam Meningkatkan Penjualan di PT Intan Pariwara Cabang Metro - Nur Septiana Hertika, Indri; Patmarina, Hepiana (CV. Lafadz Jaya, 2022)
This study examines the marketing strategy in increasing sales at PT Intan Pariwara Metro Branch. The type of research that can be used is descriptive qualitative method with interview techniques conducted to obtain company data from employees at the Metro branch office of PT Intan Pariwara. The focus of this research is how is the marketing strategy in increasing sales at PT Intan Pariwara Metro Branch? The results of the study indicate that the management of marketing strategies includes. 1) segmentation, 2) targeting, 3) positioning, 4) marketing mix. The results above are concluded as a marketing strategy in increasing sales which is currently optimal by using components of segmentation, targeting, positioning, marketing mix so as to increase revenue with good results.